Measurement of dynamic adsorption–diffusion process of methane in shale. (15th May 2016) - Wang, Jinjie; Wang, Bu'e; Li, Yajun; Yang, Zehao; Gong, Houjian; Dong, Mingzhe
Highlights: Gas dynamic adsorption–diffusion process in shale was investigated. Effects of pressure, temperature, particle size and total organic carbon were investigated. Adsorption rate constant as a function of pressure and temperature were obtained. Abstract: Shale gas is becoming an increasingly important energy resource in recent years. Identifying the gas transport process in a shale matrix is therefore of great importance in designing development strategies and in formulating the appropriate predictive mathematical models. Experimental and numerical investigations were conducted to study gas transport in shale. This paper presents the experimental work and obtains two characteristic parameters from the test results which will be utilized to serve the numerical work. Of great relevance to field development and management is knowing the contribution of each gas source to gas transport history and to ultimate gas recovery. Shale samples from Sichuan Basin in China were studied at designed conditions to test the effect of boundary pressure, temperature, particle size, and total organic content (TOC) on the dynamic adsorption–diffusion process. The tests for crushed shale samples were conducted at 35 °C, 40 °C, and 45 °C, and at test pressures up to 17 MPag. By plotting a curve describing the gas volume change per unit mass at standard condition over time ( V ad ), the adsorption–diffusion process at isothermal and constant boundary pressure (ICBP) was investigated and interpreted. These results indicate that both higher pressures and higher temperatures could promote a faster adsorption–diffusion rate, thus could promote a greater adsorption constant rate. Higher temperatures caused less gas to be adsorbed into the shale particles. Under the same experimental conditions, a difference in particle size showed no influence on the amount of gas adsorbed, but had a significant effect on the dynamic adsorption–diffusion process: the processing time extended linearly with the diameter of the particle size.